Décrire la calligraphie en caractères arabes : enjeux et méthodologies pour la constitution d’une base de données pour le projet CallFront - Vincent Thérouin; Nuria Garcia Masip; Maxime Durocher; Éloïse Brac de la Perrière (Revue des Mondes Musulmans et de la Méditerranée)
Studies on calligraphy in Arabic script have mostly focused on the central areas of the Islamicate world, where calligraphies were codified according to a precise system of regularity and proportion. However, in regions further away, a great number of calligraphic styles multiplied, using different systems of transmission and standardisation. The CallFront project investigates these lesser-known scripts by creating an online database bringing together the corpora under scrutiny. The aim of this database is to create a repertory of scripts and describe their essential features in order to establish possible formal links between corpora, despite the chronological and geographical distances. This article presents the methodology adopted for the database using Omeka and the stages followed to develop new protocols for describing calligraphy in Arabic script.